Spring protection and watercourse and its relationship with environmental quality in family property, in the Caparaó region of Espírito Santo, Brazil - Failla, Sara Carvalho; Senna, Davi Salgado de; Oliveira, Fábio Luiz de; Machado, Leonard Campos Avellar; Kobi, Hélia de Barros; Oliveira, Lidiane dos Santos Gomes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2021)
Inappropriate use and management of land has generated processes of environmental degradation, in which the increasing removal of forest coverage has impaired the hydrological cycle, water and soil quality. The objective of this work is to know the effects of the protection of the spring, and the initial part of its watercourse, on the environmental conditions in a family property. The study was carried out on the property located in the Rainha da Paz Community, in Alegre-ES, using indicators used for environmental monitoring, at the beginning in September 2013 and after one year (September 2014) of the Water Planters Project. The quality indicators used in the evaluation clearly show that the initial situation in the spring APP, and APP around the main watercourse was inadequate, in several indicators mainly due to the occupation of the area with agricultural use, specifically pasture, occurring cattle trampling within a radius of 50 meters of the spring's permanent preservation area, causing soil compaction and silting, showing a high degree of degradation, reflecting the lack of environmental adequacy, thus not complying with current environmental legislation. The project promoted improvements in the environmental conditions of the family property, through the natural regeneration of native species, bringing gains to the floristic composition, in addition to improvements in the soil conditions.